The Effect of EEG Biofeedback on the Reduction of Depression, Anxiety, Stress and Craving Beliefs in Individuals with Substance Abuse Disorder - Mohammad Narimani; Soran Rajabi (Drug Control Headquarters, Research and Education Office, 2012)
Abstract Introduction: The aim of this study is the investigation of EEG biofeedback (neurofeedback) on the reduction of depression, anxiety, stress and craving beliefs of individuals with substance abuse disorder. Method: Thirty-four males diagnosed as having substance abuse disorder (morphine addicted) were randomly assigned to experimental (N=16) and control (N=18) groups. The study used the pretest-posttest experimental and control group design. Subjects were assessed prior and subsequent to the training process on two tests of Craving Beliefs Questionnaire and Depression Anxiety Stress Scales. In this research, the analysis of variance with repeated measures was used. Findings: The results revealed that after twenty sessions of neurofeedback, a significant and clear improvement in anxiety, depression, and craving beliefs was observed, but, no significant deference between groups in stress observed. Conclusion: This study suggests that individuals with substance abuse disorder can learn to improve their anxiety, depression, and craving beliefs.